Gaussian beam diffraction in inhomogeneous media of cylindrical symmetry - Bereczyński, Paweł; Kravtsov, Yuri A.; Żegliński, Grzegorz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The method of paraxial complex geometrical optics (PCGO) is presented, which describes Gaussian beam (GB) diffraction in smoothly inhomogeneous media of cylindrical symmetry, including fibers. PCGO reduces the problem of Gaussian beam diffraction in inhomogeneous media to the system of the first order ordinary differential equations for the complex curvature of the wave front and for GB amplitude, which can be readily solved both analytically and numerically. As a result, PCGO radically simplifies the description of Gaussian beam diffraction in inhomogeneous media as compared to the numerical methods of wave optics. For the paraxial on-axis Gaussian beam propagation in inhomogeneous fibers, we compare PCGO solutions with numerical results for finite differences beam propagation method (FD-BPM). The PCGO method is shown to provide over 100-times higher rate of calculation than FD-BPM at comparable accuracy. This paper presents PCGO analytical solutions for width evolution of cylindrically symmetric GB in quadratic graded-index fiber, which is obtained in less complicated way comparing to the methods of wave optics. Besides, the influence of initial curvature of the wave front on GB evolution in graded-index fiber is discussed in this paper.
Optica Applicata, Vol. 40, 2010, nr 3, s. 705-718
Keywords: optyka; Gaussian beam diffraction; paraxial complex geometrical optics; inhomogeneous media of cylindrical symmetry